(Re) Habitar o centro histórico do Porto. - Teresa Catarina Gonçalves Pires (2013)
Hunched over Douro river, Porto enjoys of a unparalleled urban andlandscaping structure. The marks of this specificity are felt in architecture, inthe monuments, in the leisure spaces and even in the streets that draw the city.But no city is homogeneous and even in a small city as Porto's case, we find adiversity of scenarios and several diverging realities. By wandering in the city'shistorical area, it's quite evident the abandonment of buildings in general, thedegradation growth and more important than that, the lack of "Porto'spopulation".Rehabilitation as a subject in a city like Porto, it's not new, a lot hasbeen already said, written or even laid into practice. The truth is quite visibleand although many things have been made, the degrading image of thehistorical area remains. Almost 40 years have passed since CRUARB'sinterventions and more 10 years of Porto Vivo SRU's interventions, thebreaking of activity, the consequential abandonment of buildings and the lossof population, remain to be a great problem for the city's development. In full21st century, the city transforms itself in a different rhythm, everything runsfaster and more emergent, the social and individual instability is bigger andgrows more rapidly.This thesis was started by analyzing the city center's reality.Several problems were found and since then it was necessary to choosean area so that some points could be deeply studied, a superficial analysiswouldn't be enough to get to the main point: why the degradation, whynowadays it still takes place?This dissertation aims to study Reboleira Street, one of the most antiqueand relevant streets in the historical and commercial context of Porto but also one of the most degraded and abandoned in the historical center. The proximityto Cais da Ribeira makes it part of the touristic routes, tourists being the onlyones who give it life. The historical importance of the houses that compose it,although relevant for touristic purposes, seems not to be when we talk abouttemporary living.This dichotomy permanent living versus tourism is something currentlywidely discussed. It's believed that tourism can be the great development forcefor the country, but what about the population?In a time that most Portuguese and foreigner young people want indeedto live/occupy Porto's downtown, it is important to think about this balancebetween the population that actually lives there and the ones that want to live,not excluding tourism but without making it the only important point in thisstory that has been repeating itself.It's quite important to understand the tradition, the why is that piece ofthe city so relevant? And the why is it more expensive to rehabilitate instead ofbuilding new houses?To build in this moment it might not be the best solution. Both of ourhistorical, industrial and even social patrimony was replaced throughout thetimes, now only the memories of the people which today remembers of how itwas "in the good old days" remain, of how they were happy when everyoneknew each other and had a cafe, a grocery store and a job close to home.The evolution of "city", the new centers and suburbs that appearedthrough the development and expansion of it, also generated an entiredecreasing of population in the center. Throughout 50 years, Porto's historicalcenter came from too much populated to uninhabited.More than rehabilitating the buildings, it's necessary to restore the cityvalues, to generate a happy mood in society, seek for the interest in thehistorical center and revitalize a new urban dynamics, both in technical andsocial levels.